2021
DOI: 10.3390/ijms22084218
|View full text |Cite
|
Sign up to set email alerts
|

Differential miRNA Expression Profiling Reveals Correlation of miR125b-5p with Persistent Infection of Japanese Encephalitis Virus

Abstract: MicroRNAs (miRNAs) play versatile roles in multiple biological processes. However, little is known about miRNA’s involvement in flavivirus persistent infection. Here, we used an miRNA array analysis of Japanese encephalitis virus (JEV)-infected cells to search for persistent infection-associated miRNAs in comparison to acute infection. Among all differentially expressed miRNAs, the miR-125b-5p is the most significantly increased one. The high level of miR-125b-5p in persistently JEV-infected cells was confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 66 publications
2
6
0
Order By: Relevance
“…This may be because the dysregulated miRNAs are involved in the regulation of inflammation and viral response in patients. It was shown that miR-125b-5p targets STAT3 in Japanese encephalitis virus infection, thereby coordinating viral replication and host antiviral response and that when the miR-125b-5p expression was upregulated, the expression levels of target genes in persistently infected cells were both decreased, 40 it is consistent with the expression of miR-125b-5p and STAT3 in this study. STAT3 regulates a variety of biological functions and plays a key role in many cellular processes including cell growth and apoptosis, STAT3 can be up- or down-regulated in viral infections, depending on the type of virus involved.…”
Section: Discussionsupporting
confidence: 86%
“…This may be because the dysregulated miRNAs are involved in the regulation of inflammation and viral response in patients. It was shown that miR-125b-5p targets STAT3 in Japanese encephalitis virus infection, thereby coordinating viral replication and host antiviral response and that when the miR-125b-5p expression was upregulated, the expression levels of target genes in persistently infected cells were both decreased, 40 it is consistent with the expression of miR-125b-5p and STAT3 in this study. STAT3 regulates a variety of biological functions and plays a key role in many cellular processes including cell growth and apoptosis, STAT3 can be up- or down-regulated in viral infections, depending on the type of virus involved.…”
Section: Discussionsupporting
confidence: 86%
“…Persistently JEV infection increases miR-125b-5p expression and limits viral replication by dampening STAT3, MAP2K7, TRIAP1 production, which genes are associated with apoptosis and cell growth ( Huang et al, 2021 ). Overexpression of miR-124 in PK-15 cells is found to decrease the expression level of DNM2, a GTPase responsible for vesicle scission, further impairing JEV proliferation ( Yang et al, 2016 ).…”
Section: Regulation Of Mirnas In Japanese Encephalitis Virus Infectionmentioning
confidence: 99%
“…However, little is known about the effects miRNA expression may have on flavivirus-persistent infection. A miRNA array analysis of Japanese encephalitis virus (JEV)-infected cells was performed to search for persistent infection-associated miRNAs in comparison to acute infection [ 178 ]. Among all differentially expressed miRNAs, the miR-125b-5p is most significantly increased [ 178 ].…”
Section: Mechanisms Of Flavivirus Persistencementioning
confidence: 99%